Playing Beccy Cole: authenticity, performance and characters in Australian country music. Issue 1 (2nd January 2016) - Bauder, Amy
Abstract : This article explores the performance practices of Australian country music artist Beccy Cole, specifically the development of stage personas or characters as a way of situating herself within various cultural fields. Building on Erving Goffman's work on performance and everyday life (1959), Judith Butler's concept of 'performativity' and Bourdieu's practices and habitus, my analysis reveals the practices that produce the public personas or characters. Critiquing the expectation, or even requirement, of honesty in country music, this article argues that characters of Beccy Cole work to disrupt notions of authenticity in performance in the Australian country music community. The 'literal staginess' of Beccy's characters provides an entry point for critiquing the ways in which the 'real' and 'authentic' are privileged in country music.